Strategi Komunikasi Pemasaran dalam Penggunaan Media Sosial Instagram Casa Plants and Coffee Pondok Cabe Tangerang Selatan - Rahmayanti, Rahmayanti; Anggraini, Katry; Benazir, Dyas Mulyani (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
In the digital era, social media has become an essential platform for business promotion, shifting traditional marketing toward digital channels. This study aims to examine the use of Instagram in promoting Casa Plants and Coffee, located in Pondok Cabe Pamulang, South Tangerang, and to analyze the marketing communication strategies implemented through this social media platform. Employing a qualitative case study approach, data were collected through purposive sampling involving the business owner, social media managers, and active followers of Casa Plants and Coffee’s Instagram account. Data collection methods included in-depth interviews, direct observation of Instagram content and interactions, as well as questionnaires to capture follower perceptions and responses. The data were analyzed descriptively to evaluate the effectiveness of Instagram as a marketing communication tool. The findings reveal that Instagram’s diverse user base, ranging from teenagers to adults and various community groups, serves as an effective medium for visual storytelling through images and videos, enhancing product awareness in line with cognitive marketing concepts. The account’s caption language is crafted to be clear, engaging, and encourages follower interaction. Furthermore, the @casa.plants Instagram account facilitates direct communication and collaboration with communities, leveraging user-generated content to broaden promotional reach. This study underscores Instagram’s strategic role in building brand identity and enhancing customer engagement for Casa Plants and Coffee.